Search for neutral Higgs bosons decaying into four taus at LEP2 - Schael, Stefan; Hanke, Paul; Hepp, Volker; Kluge, Eike-Erik; Tittel, Klaus (Journal of high energy physics, 2010)
A search for the production and non-standard decay of a Higgs boson, h, into four taus through intermediate pseudoscalars, a, is conducted on 683 pb−1 of data collected by the ALEPH experiment at centre-of-mass energies from 183 to 209 GeV. No excess of events above background is observed, and exclusion limits are placed on the combined production cross section times branching ratio, $ {ξ^2} = \frac{{σ \left( {{\text{e}^{+} }{\text{e}^{-} } → {\text{Zh}}} \right)}}{{{σ_{\text{SM}}}\left( {{\text{e}^{+} }{\text{e}^{-} } → {\text{Zh}}} \right)}} × B\left( {h → {\text{aa}}} \right) × B{\left( {{\text{a}} → {τ^{+} }{τ^{-} }} \right)^2} $. For mh < 107 GeV/c2 and 4 < ma < 10 GeV/c2, ξ2 > 1 is excluded at the 95% confidence level.